Analisis Swot dalam Perspektif Al-Qur’an - Al Masithoh, Silvinatin (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2023)
The aim of this research is that the Al-Qur'an is a holy book that contains various solutions to all problems in life. Thousands of verses in it can be used as a guide to life, in accordance with the name of the Al-Quran, namely